2006
DOI: 10.1227/01.neu.0000228680.22550.a2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Long-term Outcome in Poor-grade Aneurysmal Subarachnoid Hemorrhage

Abstract: Outcome in poor-grade aneurysmal SAH is strongly predicted by patient age, worst preoperative Hunt and Hess clinical grade, and aneurysm size. Hyperglycemia on admission after poor-grade aneurysmal SAH increases the likelihood of poor outcome, and is a potentially modifiable risk factor. The Prognosis Score is a useful tool for preoperatively assessing the likelihood of a favorable outcome for poor-grade aneurysmal SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 39 publications
7
109
1
Order By: Relevance
“…In addition to supporting the well-accepted association between clinical grade at admission and outcome, 2,9,20,24,31,38,41 our results demonstrate the impact of cerebral ischemia on delayed recovery at all time points. Although the presence or absence of any stroke was not predictive of a patient's capacity to recover, the avoidance of a large (> 4 cm) stroke or ischemia in eloquent territory was highly predictive of delayed improvement.…”
Section: Figsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to supporting the well-accepted association between clinical grade at admission and outcome, 2,9,20,24,31,38,41 our results demonstrate the impact of cerebral ischemia on delayed recovery at all time points. Although the presence or absence of any stroke was not predictive of a patient's capacity to recover, the avoidance of a large (> 4 cm) stroke or ischemia in eloquent territory was highly predictive of delayed improvement.…”
Section: Figsupporting
confidence: 84%
“…This is consistent with prior studies demonstrating an association between younger age and more favorable outcomes following SAH. 10,11,14,20,24,31 Although patients 65 years of age or younger had more than 5 times the odds of improvement beyond 6 months, when improvement specific to the time intervals beyond 1 year was analyzed, age was no longer a significant predictor. This finding suggests that while younger age has its benefits in recovery, the most delayed improvement is driven primarily by other factors.…”
Section: Figmentioning
confidence: 98%
“…There are, however, theoretical advantages to early occlusion for aneurysms in poor-grade patients. Re-bleeding is more frequent with a poor grade and larger aneurysm size 9,11,13,15 . The incidence of vasospasm is greater in poor-grade patients: optimum therapy is best performed after aneurysm occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that age and initial Glasgow Coma Scale (GCS) can predict outcomes, but none have validated the exclusion criteria for aggressive treatment in patients with high-grade SAH. 9,11,12,14,[18][19][20]22,25,26) The present study describes the anatomical and clinical findings during surgical treatment of poorgrade ruptured MCA aneurysms, and tailored surgical strategies based on the distribution of hematoma. The three study objectives are to identify patients with the worst neurological status prior to treatment who were able to achieve useful daily life; to follow functional outcomes and living status in patients who underwent aggressive treatment; and to describe the surgical procedures and how these were employed in our clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5,6,17,19,29,34) Patients do not always achieve outcomes consistent with their initial neurological status, and 50-60% of patients affected by rupture of an intracranial aneurysm can become functional survivors. 3,[9][10][11][12]14,18,20,22,25,26) However, insufficient surgical intervention may result in loss of potentially salvageable function or life. 1,3,9,12,15,26,27) Adequate treatment often requires hematoma evacuation and decompressive maneuvers in addition to clipping procedures.…”
Section: Introductionmentioning
confidence: 99%